Ethanol Alleviates Amyloid-β-Induced Toxicity in an Alzheimer’s Disease Model of Caenorhabiditis elegans - Bai, Shuju; Wang, Wenbo; Zhang, Zhiwei; Li, Mengyao; Chen, Zehan; Wang, Jiuqiao; Zhao, Yanlin; An, Lu; Wang, Yuxiang; Xing, Shu; Fu, Xueqi; Ma, Junfeng (Frontiers in Aging Neuroscience, 2021)
Amyloid-β, a hallmark of Alzheimer’s disease, forms toxic intracellular oligomers and extracellular senile plaques resulting in neuronal toxicity. Ethanol is widely consumed worldwide. Moderate ethanol consumption has numerous benefits in humans. We found that ethanol could significantly extend the lifespan of Caenorhabiditis elegans in a previous study. Based on that study, we tested the effect of ethanol on Alzheimer’s disease transgenic Caenorhabiditis elegans strain CL4176, which expresses amyloid-β1-42 peptide in body wall muscle cells. Ethanol delayed paralysis and reduced amyloid-β oligomers in Caenorhabiditis elegans worms of the CL4176 strain. Moreover, ethanol could induce the nuclear translocation of DAF-16 in the nematodes. However, in worms that were fed daf-16 RNAi bacteria, ethanol no longer delayed the paralysis. The qPCR assays showed that ethanol increases the expression of daf-16, hsf-1 and their common target genes- small heat shock protein genes. In addition, we also found that ethanol could increase lysosome mass in the CL4176 worms. In summary, our study indicated that ethanol attenuated amyloid-β toxicity in the Alzheimer’s disease model of Caenorhabiditis elegans via increasing the level of lysosomes to promote amyloid-β degradation and upregulating the levels of small heat shock protein genes to reduce amyloid-β aggregation.